HDAC-an important target for improving tumor radiotherapy resistance - Ling, Rui; Wang, Jingzhi; Fang, Yuan; Yu, Yunpeng; Su, Yuting; Sun, Wen; Li, Xiaoqin; Tang, Xiang (Frontiers in Oncology, 2023)
Radiotherapy is an important means of tumor treatment, but radiotherapy resistance has been a difficult problem in the comprehensive treatment of clinical tumors. The mechanisms of radiotherapy resistance include the repair of sublethal damage and potentially lethal damage of tumor cells, cell repopulation, cell cycle redistribution, and reoxygenation. These processes are closely related to the regulation of epigenetic modifications. Histone deacetylases (HDACs), as important regulators of the epigenetic structure of cancer, are widely involved in the formation of tumor radiotherapy resistance by participating in DNA damage repair, cell cycle regulation, cell apoptosis, and other mechanisms. Although the important role of HDACs and their related inhibitors in tumor therapy has been reviewed, the relationship between HDACs and radiotherapy has not been systematically studied. This article systematically expounds for the first time the specific mechanism by which HDACs promote tumor radiotherapy resistance in vivo and in vitro and the clinical application prospects of HDAC inhibitors, aiming to provide a reference for HDAC-related drug development and guide the future research direction of HDAC inhibitors that improve tumor radiotherapy resistance.